고크롬 백주철의 미세조직과 기계적 특성에 미치는 초기응고 조직의 영향 - 조현욱; Hyun Wook Jo; 도정현; Jeong Hyeon Do; 조원제; Won Je Jo; 정현득; Hyun Deuk Chung; 이재현; Je Hyun Lee; 조창용; Chang Yong Jo (한국주조공학회지, 2015)
Due to excellent abrasion resistance the high-chrome white irons are widely used in mining and mineral industries. Minor variation of carbon content in 28% chrome white iron resulted in difference in primarily solidified microstructure. Sub-eutectic (hypoeutectic) a) composition led to formation of primarily solidified dendrites. Formation of primarily solidified dendrites which were supersaturated with carbon and chrome also caused precipitation of fine secondary carbides that are different from relatively large plate type M7C3 carbides in the eutectic structure. Small portion of primarily solidified dendrite expected to contribute significantly to the improvement of abrasion resistance of the white iron because the dendrites provided mechanical support to carbides. The relative fraction of primary dendrite increased with reduction of carbon content from the eutectic composition. The increased fraction of primary dendrite increased hardness value of the white irons.